JENIS-JENIS SERANGGA NOCTURNAL PADA TANAMAN DUKU (Lansium domesticum Corr.) DI DESA SRIGENI LAMA KABUPATEN OKI PROVINSI SUMATERA SELATAN - Dian Mutiara (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2015)
The research about  identification insects at duku (Lansium domesticum Corr.) plantation was conducted at Serigeni Lama Kayuagung village on  September till October 2014. The objective of this research was collect insects at duku. This research utilited the direct observation method during two moon. This method used insecting net, light traps and fit fall traps. The result of the identification  geted 7 Order, 14 Family, 15 Genera, dan 15 Spesies. Key words : Identification, insects, Lansium domesticum Corr